LEARN TO GRASP ASSESSMENT NOT MERELY AS A DEVICE FOR STUDENT EVALUATION, BUT AS AN IMPERATIVE STRATEGY FOR TODAY’S EVERYDAY CLASSROOM LEARNING TO ENHANCE STUDENTS LEARNING AND SKILLS - Seema, Shahzadi; Reba, Amjad (International Journal of Psychosocial Rehabilitation, 2020)
--Learn to grasp assessment, not merely as a device for student evaluation, but as an imperative strategy for everyday classroom learning and has a significant effect on improving students learning and skills. So, if concern is the change in students learning then there is a need to see the assessment with new eyes. The study was designed with the objectives, to bring on record the views of teachers about the use of classroom assessment practices in improving learning and developing skills at public sector universities of Khyber Pakhtunkhwa (KP) at Undergraduate four years’ programs. The sample of this qualitative research comprises 20 teachers, 4 teachers each from five sampled public sector universities in KP. To get the relevant information a semi-structured interview schedules were used from teachers of the sampled universities. To analyze data, thematic approach was used. The study resulted in, that almost all of the teachers were highly satisfied with the use of different assessment practices for the purpose of improving students learning and developing skills and have a very positive impact on the developing life skills among students.